The Concept of the Mathematical Literacy - Dudaitė, Jolita (Acta Paedagogica Vilnensia, 2007)
The main idea of the article is to define the concept of the mathematical literacy. This is the new and transforming concept, the definition of which depends on the time, culture, and traditions of the particular country. The importance of the mathematical literacy in the modem society is shown in the article. In different countries or used by different scholars mathematical literacy has the different names. The most popular terms arc numeracy, quantitative literacy, and mathematical literacy. But the following terms can be also find: quantitative reasoning, quantitative practices, mathematical proficiency, mathematical competencies, mathematical power, matheracy, mathemacy, functional numeracy, functional mathematics and so on. The differences and similarities between those terms arc analysed. The difference between mathematics and mathematical literacy is shown in the article. Mathematics is understood as having such attributes: general, abstract, depending on the context very little, independent from the society, apolitical, in the centre are formulas and relations, uses methods and algorithms, well-defined problems, exact computation, subject based, problem-solving, few possibilities for practice, predictable. Mathematical literacy is understood a5 having following attributes: specific and concrete, real, with changeable context, depending on the context very much, depending on the society, political, in the centre - data, uses ,,ad hoe" method, problems are not well-defined, approximation, between subjects, problem-describing, a lot of possibilities for practice, unpredictable. The analysis of diverse concept of mathematical literacy definitions is presented. There is no best definition of the concept, nor even the most popular definition of the concept. Each country, each scientist use the definition which seems to be the best for the particular country, for the particular time and for the particular person. The components of the mathematical literacy concept is given in the article. These arc universality, relevance of the themes, logical (or mathematical, or critical) thinking, mathematical argument, problem solving, number sense, symbol sense, special thinking, practical skills, data interpretation, basic mathematical knowledge, cultural aspect, confidence with mathematics, mathematical communication, data and results representation, work with information, experimentation, modelling, using tools and technology, attitudes. The model of the mathematical literacy concept is created in the article.
Keywords: mathematics; mathematics education; mathematical literacy; model of the mathematical literacy